Priority areas for cannabis and cannabinoid product research in South Africa - Tanya N. Augustine; Carel J. Cairns; Sean Chetty; Lisa G. Dannatt; Nadine Gravett; Glenda Grey; Gerhard Grobler; Zukiswa Jafta; Peter Kamerman; John Lopes; Motlalepula G. Matsabisa; Pierre Mugabo; et al. (AOSIS, 2018)
No abstract available.